2019
DOI: 10.1186/s41016-019-0163-x
|View full text |Cite|
|
Sign up to set email alerts
|

Clipping versus coiling in posterior circulation intracranial aneurysms: a meta-analysis

Abstract: Background: Posterior circulation intracranial aneurysm (IA) treatment remains challenging, due to the anatomy of the area and the high rupture possibility. Endovascular treatment seems to be more suitable for these aneurysms, but studies focused on endovascular treatment demonstrate a high rate of re-intervention needing. A meta-analysis might offer a clearer view, being useful in a more effective treatment planning. Methods: A systematic search was performed, using the PubMed database platform. The final art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…However, the choice of treatment modality ought to consider factors including patient characteristics, aneurysm morphology and location, and physician expertise. 11 This case report adds to the limited literature describing unruptured PCA aneurysms presenting with seizures. This patient was significantly older than previous cases, and he experienced focal aware seizures consistent with temporal lobe epilepsy for some time before seeking medical care.…”
mentioning
confidence: 65%
“…However, the choice of treatment modality ought to consider factors including patient characteristics, aneurysm morphology and location, and physician expertise. 11 This case report adds to the limited literature describing unruptured PCA aneurysms presenting with seizures. This patient was significantly older than previous cases, and he experienced focal aware seizures consistent with temporal lobe epilepsy for some time before seeking medical care.…”
mentioning
confidence: 65%
“…When it comes to the recurrence rate of aneurysms, there was a difference between transcranial surgery and EVT in our series, with the recurrence rate of EVT being higher than that of transcranial surgery (39.5% vs 11.1%, p=0.03). Tsianaka et al 12) also reported a high recurrence rate for EVT in posterior circulation aneurysms. In our experience, when it comes to the durability of treatment, transcranial surgery is better than EVT in large unruptured posterior circulation aneurysms.…”
Section: Discussionmentioning
confidence: 96%
“…There has been relentless debate over the superiority of transcranial surgery or EVT for intracranial aneurysm. In a recent meta-analysis, Tsianaka et al 12) reported no superiority between transcranial surgery and EVT in the treatment of posterior circulation aneurysm. However, their report lacked a subgroup analysis for large posterior circulation aneurysms 12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mortality rates at one year did not reveal any significant differences [ 5 ]. A meta-analysis on coiling versus clipping of posterior circulation aneurysms in 2019 concluded that neither method was superior to the other in preventing permanent neurologic deficits [ 6 ]. One study assessing the clipping of 47 PICA aneurysms had no mortalities and only 2.1% morbidity (one patient) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%